High-dose treosulfan and melphalan as consolidation therapy versus standard therapy for high-risk (metastatic) ewing sarcoma - Koch, Raphael; Gelderblom, Hans; Haveman, Lianne; Brichard, Benedicte; Jürgens, Heribert; Cyprova, Sona; van den Berg, Henk; Hassenpflug, Wolf; Raciborska, Anna; Ek, Torben; Baumhoer, Daniel; Egerer, Gerlinde; et al. (Journal of clinical oncology, 2022)
PURPOSE - - Ewing 2008R3 was conducted in 12 countries and evaluated the effect of treosulfan and melphalan high-dose chemotherapy (TreoMel-HDT) followed by reinfusion of autologous hematopoietic stem cells on event-free survival (EFS) and overall survival in high-risk Ewing sarcoma (EWS). - - METHODS - - Phase III, open-label, prospective, multicenter, randomized controlled clinical trial. Eligible patients had disseminated EWS with metastases to bone and/or other sites, excluding patients with only pulmonary metastases. Patients received six cycles of vincristine, ifosfamide, doxorubicin, and etoposide induction and eight cycles of vincristine, actinomycin D, and cyclophosphamide consolidation therapy. Patients were randomly assigned to receive additional TreoMel-HDT or no further treatment (control). The random assignment was stratified by number of bone metastases (1, 2-5, and > 5). The one-sided adaptive-inverse-normal-4-stage-design was changed after the first interim analysis via Müller-Schäfer method. - - RESULTS - - Between 2009 and 2018, 109 patients were randomly assigned, and 55 received TreoMel-HDT. With a median follow-up of 3.3 years, there was no significant difference in EFS between TreoMel-HDT and control in the adaptive design (hazard ratio [HR] 0.85; 95% CI, 0.55 to 1.32, intention-to-treat). Three-year EFS was 20.9% (95% CI, 11.5 to 37.9) in TreoMel-HDT and 19.2% (95% CI, 10.8 to 34.4) in control patients. The results were similar in the per-protocol collective. Males treated with TreoMel-HDT had better EFS compared with controls: median 1.0 years (95% CI, 0.8 to 2.2) versus 0.6 years (95% CI, 0.5 to 0.9); P = .035; HR 0.52 (0.28 to 0.97). Patients age < 14 years benefited from TreoMel-HDT with a 3-years EFS of 39.3% (95% CI, 20.4 to 75.8%) versus 9% (95% CI, 2.4 to 34); P = .016; HR 0.40 (0.19 to 0.87). These effects were similar in the per-protocol collective. This observation is supported by comparable results from the nonrandomized trial EE99R3. - - CONCLUSION - - In patients with very high-risk EWS, additional TreoMel-HDT was of no benefit for the entire cohort of patients. TreoMel-HDT may be of benefit for children age < 14 years.
Gesehen am 29.08.2022